The influence of through-thickness reinforcement geometry and pattern on delamination of fiber-reinforced composites: Part II – Modeling. (1st December 2017) - Pappas, Georgios; Joncas, Simon; Michaud, Véronique; Botsis, John
Abstract: This article reports modeling techniques and results based on experimental Mode I characterization of a layered woven GFRP material with tufting reinforcement. Standard tuft and loop-less geometries are investigated on three different areal patterns to evaluate their effects on fracture resistance. The experiments reveal that tow/ply and tuft bridging phenomena are present during delamination. The numerical modeling comprises cohesive elements for tow/ply bridging and 1D connector elements for discrete tufts. The traction separation relations for the cohesive model are acquired using an inverse scheme based on strain measurements and the force-separation relations of tuft's failure mechanisms from uniaxial pulling tests on a reference tufting pattern. Results show that tuft's failure mechanism is strongly affected by tufting pattern and geometry while tow/ply bridging contributes 20–30% of the overall fracture energy. The energy absorbed by pull-out of loop-less tufts is approximately twice the fracture energy of standard ones with pull-out triggering much more extensive tow/ply bridging phenomena.